Developing Emotional Intelligence and Competencies to Strengthen the Performance of Project Managers at the Indonesian National Construction Implementation Association East Java - Erman Hernadi; Lilik Kustiani; Bambang Supriadi (LPPM Institut Teknologi dan Sains Mandala, 2025)
This study investigates the role of emotional intelligence and managerial competencies in enhancing project manager performance, with job attitude as a mediating variable, within construction companies under the Indonesian National Construction Implementation Association in East Java. Using a quantitative approach and surveying 182 project managers, the study assesses key constructs such as emotional intelligence (self-awareness, self-management, social awareness, and relationship management), managerial competencies (motives, traits, self-concept, and knowledge), job attitudes (commitment, satisfaction, involvement), and project performance (quality, quantity, timeliness, and cooperation). The findings reveal that emotional intelligence significantly affects project manager performance, particularly through improved self-awareness and social relationship skills. However, managerial competencies alone do not substantially influence performance unless supported by positive job attitudes. The study confirms that job attitude is a critical bridge linking emotional intelligence to improved performance outcomes. These findings underscore the importance of soft skills development in construction project environments and offer practical insights for enhancing leadership training, team dynamics, and project success rates. The study provides strategic recommendations for organizational growth and workforce management within Indonesia’s construction sector.